An Investigation of Afghan Undergraduate English Major Students’ Academic Writing Difficulties - Noori, Abdullah (Universitas Muhammadiyah Yogyakarta, 2020)
Academic Writing is a core subject that undergraduate students take during their four years of study. However, many students find the subject challenging. Several studies have been conducted to explore the difficulties students face, yet in Afghanistan, little to no research is available. Hence, this project is a small attempt to address this gap. This research aims to look into the difficulties of undergraduate English major students face in Academic Writing. The writing difficulties were investigated in terms of content, structure, and language. A quantitative descriptive method was employed for this study, and a questionnaire was given to 121 undergraduate degree students from the English Department at Kabul University. The research data were analyzed using SPSS. The research findings revealed that the students faced several challenges in Academic Writing in terms of language, structure, and content. Finally, some recommendations to overcome the difficulties and suggestions for future research are provided.